Tidak Ada Penyakit Menular: Praktik Dakwah Jamaah Tabligh dan Pengaruhnya terhadap Penyebaran Covid-19 - Inayatul Mustautina (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2020)
This research discussed the conversion of Jama'ah Tabligh Bantarkawung, Brebes, Central Java, and its effects on the spread of Covid-19. In this case, the phenomenon of Jama'ah Tabligh's preaching activity produced a wide variety of reactions. The methods employed in this study combines field research with literature. The results in this paper are; first, the practice of Jama 'ah Tabligh preaching at Bantarkawung that attended the Ijma' Ulama' Jamaah Tabligh at Gowa during the Covid-19 pandemic. Second, there is a say that there is no contagious disease, if it is contagious, then it must be transmitted by God's will. Third, the approximately 27 person of Jama'ah Tabligh Bantarkawung who attended Ijtima Ulama' Gowa, 17 person were positively Covid-19 proved by rapid test. Then, 13 person tested positive for swab tests that made their home area become Covid-19 red zone.